Copper Ions Induce DNA Sequence Variation in Zygotic Embryo Culture-Derived Barley Regenerants - Orłowska, Renata; Zimny, Janusz; Bednarek, Piotr T. (Frontiers in Plant Science, 2021)
In vitro tissue culture could be exploited to study cellular mechanisms that induce sequence variation. Altering the metal ion composition of tissue culture medium affects biochemical pathways involved in tissue culture-induced variation. Copper ions are involved in the mitochondrial respiratory chain and Yang cycle. Copper ions may participate in oxidative mutations, which may contribute to DNA sequence variation. Silver ions compete with copper ions to bind to the complex IV subunit of the respiratory chain, thus affecting the Yang cycle and DNA methylation. The mechanisms underlying somaclonal variation are unknown. In this study, we evaluated embryo-derived barley regenerants obtained from a single doubled-haploid plant via embryo culture under varying copper and silver ion concentrations and different durations of in vitro culture. Morphological variation among regenerants and the donor plant was not evaluated. Methylation-sensitive Amplified Fragment Length Polymorphism analysis of DNA samples showed DNA methylation pattern variation in CG and CHG (H = A, C, or T) sequence contexts. Furthermore, modification of in vitro culture conditions explained DNA sequence variation, demethylation, and de novo methylation in the CHG context, as indicated by analysis of variance. Linear regression indicated that DNA sequence variation was related to de novo DNA methylation in the CHG context. Mediation analysis showed the role of copper ions as a mediator of sequence variation in the CHG context. No other contexts showed significant sequence variation in mediation analysis. Silver ions did not act as a mediator between any methylation contexts and sequence variation. Thus, incorporating copper ions in the induction medium should be treated with caution.